RESPONSE ANALYSIS OF MODAL COUPLING SYSTEM CAUSED BY ROUGH MICRO SURFACE - XIA BingXin; LI JiPing; YU LianZhou; PAN WuJiu (Jixie qiangdu)
In view of the complexity of the surface instability noise mechanism of the braking system, scholars have carried out a lot of research from the theoretical and experimental perspectives. The purpose was to reveal the instability and nonlinear response mechanism of rough micro contact surfaces to modal coupled self-excited vibration systems. For the modeling of contact surface stiffness, the fractal theory that can simulate the fractal characteristics of machined surfaces was introduced, and the model was embedded into the two-degree-of-freedom brake system model, thus a dynamic model of the brake system containing microscopic contact characteristics parameters was established. The influence of fractal parameters on the stability and nonlinear response of the system was analyzed. Theoretical and experimental studies have found that both fractal dimension D and fractal roughness G have an important influence on the braking stability of the system. This study can provide a reference for the dynamic analysis of similar micro contact effects on macro mechanical systems in engineering.